Type Of Reading Comprehension Question In EnglishNational Examination Of Senior High SchoolIn 2011-2015 - Dian Yusniati, Febriana, Prof. Dr. EndangFauziati, M. Hum, Aryati Prasetyarini S.Pd., M. Pd (2016)
This study is carried out to describe the types of reading comprehension question in English National Examination of Senior High School in 2011-2015.It aims to describe: (1) the type of reading comprehension tested in 201-2015 English State Examination at Senior High School, (2) the similarity of type of reading comprehension tested in 2011-2015 English State Examination at Senior High School and (3) the difference of type of reading comprehension tested in 2013 English State Examination at Senior High School. The type of this research is content analysis research. The researcher gets the data from document of English National Examination Paper. The collecting data technique is documentat analysing. The result of this study shows that: 1) the types of reading comprehension question in 2011-2015 consists of question about the idea of the passage, directly answered question, indirectly answered question, vocabulary question, and overall review question. 2) the similarity of the types of question are about the total of type in every year and the form of the question. 3) the difference of the types of question is on the variation of question. The conclusion of this study is the dominant type of reading comprehension in English National Examination of Senior High School is directly answered question, with the percentage in 2011th 40%, in 2012th 54%, in 2013th 66%, in 2014th 37% and in 2015th 31%.